KAJIAN ETNOBOTANI TUMBUHAN SEBAGAI BAHAN TAMBAHAN PANGAN SECARA TRADISIONAL OLEH MASYARAKAT DI KECAMATAN PEKUNCEN KABUPATEN BANYUMAS - Ari Apriliani; Sukarsa Sukarsa; Hexa Apriliana Hidayah (Scripta Biologica, 2014)
People can’t detached from plants in fulfilling their needs, such as plant as food additives. This study aimed to know the types and parts of plants as food additives, and its benefits, as well as its utilization by people of Pekuncen District Banyumas Regency. This research used survey method with purposive random sampling and semi-structured interviews. Data were analyzed descriptively. The results of this study indicated 34 species of 19 familia plants used as food additives. The part of plants used as food additives were tubers, rhizomes, seeds, stems, leaves and fruits. Food additive plants were utilized as flavor enhancer, natural dye, preservatives and acid flavor. The plants were utilized by cooking, cuting, crushing, shredding, grinding, "dikeprek", roasting, boiling, and marinating.